Management and Organizational Behavior / Third Edition - Cook Curtis W; Hunsaker Phillip L (Mcgraw Hill Irwin, 2001)
What Managers and Organizations Do, Managing People and Organizations, Strategic Thinking and Planning and Continuous Improvement, Organizing Work and People, Creating and Modifying Organizational Culture, Managing People, Understand(Sl(Bng Perception and Learning and Personality, Motivation Principles, Motivation Methods and Applications, Managing Behavior Between People, Communicating for Understanding and Results, Creating Productive Interpersonal Relations, Building Groups into Teams, Conflict Management and Negotiation, Leadership Practices, Ethical Problem Solving and Decision Making, Power and Politics, Leadership, Managing Change, Organizational Change and Development and Innovation, Self-Management at Work: Managing Careers and Stress, Appendix, Notes, Glossary, Index.s
What Managers and Organizations Do, Managing People and Organizations, Strategic Thinking and Planning and Continuous Improvement, Organizing Work and People, Creating and Modifying Organizational Culture, Managing People, Understand(Sl(Bng Perception and Learning and Personality, Motivation Principles, Motivation Methods and Applications, Managing Behavior Between People, Communicating for Understanding and Results, Creating Productive Interpersonal Relations, Building Groups into Teams, Conflict Management and Negotiation, Leadership Practices, Ethical Problem Solving and Decision Making, Power and Politics, Leadership, Managing Change, Organizational Change and Development and Innovation, Self-Management at Work: Managing Careers and Stress, Appendix, Notes, Glossary, Index.s